Echocardiographic features of eosinophilic endomyocardial disease. Issue 5 (November 1982) - Davies, J; Gibson, D G; Foale, R; Heer, K; Spry, C J; Oakley, C M; Goodwin, J F
Abstract : Nine patients with eosinophilic endomyocardial disease who had undergone angiocardiography with histological staging of their disease, were studied by M-mode and two dimensional echocardiography to determine the extent to which specific features of the disease could be evaluated by these non-invasive methods. In seven patients, amplitude processed two dimensional echocardiography showed regions where the relative intensity of endomyocardial echoes was greater than normal, and their distribution corresponded to known areas of fibrosis. Standard two dimensional echocardiography was normal in all but three patients. In eight patients M-mode echocardiography showed only non-specific abnormalities, but appeared to be useful in assessing the functional consequences of myocardial or mitral valve disease. After digitisation a reduction in the duration and an increase in the peak rate of dimension increase during filling was prolonged. It was concluded that amplitude processed two dimensional echocardiography might be useful in diagnosing the extent and severity of endomyocardial disease in patients with hyperosinophilia. These noninvasive techniques may thus provide a means for the early diagnosis of endomyocardial fibrosis and could be useful in assessing in progression or response to treatment.